ANALISIS DISKRIMINAN TINGKAT LITERASI KEUANGAN MAHASISWA DALAM MENGELOLA KEUANGAN PRIBADI (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam dan Mahasiswa Fakultas Tarbiyah dan Keguruan UINAM Angkatan 2014) - ., Ismawati; ., Norwahida (Idaarah: Jurnal Manajemen Pendidikan, 2018)
This study aims to determine whether there are differences in the level of financial literacy students of Faculty of Economics and Islamic Business and Faculty of Tarbiyah and Teacher Training UINAM 2014 based on Sex, Study Program and Parent Income. Objects studied are students of the Faculty of Economics and Islamic Business as a student who has a good level of financial literacy and students of the Faculty of Tarbiyah and Teacher Training as a student who has a lack of good financial literacy level UINAM 2014 Force. This research is a quantitative research. The sample used in this study as many as 302 people. Sampling technique by stratified random sampling (random sample). This study uses Discriminant Analysis (Two Group Discriminant) with the help of SPSS Version program. 22. This study obtained the result that there are differences in the level of financial literacy of Faculty of Economics and Islamic Business and Faculty of Tarbiyah and Teacher Training UINAM force 2014 based on Gender, there is difference of financial literacy level of student of Faculty of Economics and Islamic Business and Faculty of Tarbiyah and UINAM Class of 2014 based on Study Program and there is no difference in the level of financial literacy of Faculty of Economics and Business of Islam and Faculty of Tarbiyah and UGM Training for class of 2014 based on Parents Revenue. Discriminant test result stated that Sex and Study Program have significant effect simultaneously to the difference of financial literacy level of student of Faculty of Economics and Business of Islam and Faculty of Tarbiyah and UGM Training of class of 2014 whereas Parent Revenue is not.